CONCENTRATIONS OF Zn, Cu and Pb IN THE MUSCLE OF TWO EDIBLE FINFISH SPECIES IN AND AROUND GANGETIC DELTA REGION: Life Sciences-Ecology - Shankhadeep Chakraborty; Sujoy Biswas; Kakoli Banerjee; Abhijit Mitra (International Journal of Life Science and Pharma Research, 2022)
We analysed concentrations of zinc, copper and lead in the muscle of two commercially important finfish species namely, Liza parsia and Liza tade in the western and central sectors of Gangetic delta region during 14th to 19th March, 2016 using Atomic Absorption Spectrophotometer. Metal accumulation followed the order Zn > Cu > Pb. Between the two species, the degree of metal accumulation was found to be in the order Liza parsia > Liza tade, which may be the result of difference in their food habit or degree of exposure to ambient media contaminated with heavy metals. Heavy metals in the edible parts of the investigated finfish species were compared with the permissible safety levels for human uses.